Android Recipes A Problem-Solution Approach - Smith, Dave; Friesen, Jeff (Apress : Imprint: Apress, 2014)
Android continues to be one of the leading mobile OS and development platforms driving today's mobile innovations and the apps ecosystem. Android appears complex, but offers a variety of organized development kits to those coming into Android with differing programming language skill sets. Android Recipes: A Problem-Solution Approach, Third Edition offers more than 100 down-to-earth code recipes, and guides you step-by-step through a wide range of useful topics using complete and real-world working code examples. It's updated to include the KitKat Android 4.4 SDK as well as earlier releases. Instead of abstract descriptions of complex concepts, in Android Recipes, you'll find live code examples. When you start a new project you can consider copying and pasting the code and configuration files from this book and then modifying them for your own customization needs. Crammed with insightful instruction and helpful examples, this third edition of Android Recipes is your guide to writing apps for one of today's hottest mobile platforms. It offers pragmatic advice that will help you get the job done quickly and well. This can save you a great deal of work over creating a project from scratch!